Persepsi Masyarakat Mengenai Peraturan Larangan Mudik Selama Covid-19 - Andian Fadhil Nugraha Andi (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
ABSTRACT This research focuses on discussing public perceptions regarding the regulations on the prohibition of going home during COVID-19. This ban was carried out by the government in order to cut the rate of transmission of the Covid virus so that it does not spread further. The purpose of this study was to determine the public's perception of the regulations on the prohibition of going home during COVID-19. To answer these objectives, researchers used a qualitative descriptive study. Methods of data collection through online interviews and document review. Interviews with informants, namely people in the city of Bandung. Meanwhile, a document review is carried out to strengthen the theoretical references related to research problems. Informants were determined based on purposive technique. The informants in this study became the foundation in collecting data to uncover research problems. The selection of informants certainly has certain criteria, the emphasized criteria are students and overseas workers who understand the government regulations to prohibit going home during COVID-19. The results of this study indicate that the regulations on the prohibition of going home by the government have given a positive response. Bandung city community agrees with this homecoming ban because it is believed to be a strategy for preventing and spreading the COVID-19 virus. They agreed not to do homecoming because it was feared that travelers could become a new cluster of corona virus transmission when returning to their hometowns Keywords: Homecoming; Pandemic; Public Perception